CYBER COUNSELING: MEDIA & SOLUSI LAYANAN KONSELING DI TENGAH PANDEMI COVID-19 - Sukamto, Sukamto; suryadi, suryadi Suryadi (UIN Sunan Kalijaga Yogyakarta, 2022)
Information and communication technology is developing rapidly in the era of globalization. Online media and sites are often used as tools to carry out a job, especially in the era of the COVID-19 pandemic. During the pandemic, psychological complaints are increasing, so this cyber counseling service can be a solution related to these psychological problems. This study was conducted to determine the use of cyber counseling in the midst of the covid-19 pandemic, as well as the media it uses. The method used in this research is literature study. The results of the study show that cyber counseling services can be a solution or alternative for counseling during the COVID-19 pandemic which requires us to reduce direct interactions. With cyber counseling, counselees do not need to meet face to face to get counseling services but can easily access counseling services using currently available online media. Cyber counseling uses virtual media such as chat, video conferencing, websites, or applications in conducting the counseling process. Keywords: Cyber Counseling, Counseling Era Pandemic, Virtual Counseling